2011
DOI: 10.5586/asbp.2004.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of lnula royleana DC

Abstract: A micropropagation method, through axillary shoot proliferation, was elaborated for Inula royleana DC. (Asteraceae), a medicinal plant native of Himalaya. Primary explants (cotyledonary node explants) and secondary explants (node explants of in vitro regenerated shoots) of the plant, inoculated on MS medium supplemented with 0.1 µM NAA and 5.0 µM kinetin, regenerated 3.4 ± 1.2 and 5.1 ± 1.9 axillary shoots per explant, respectively. The regenerated shoots were easily rooting and adapting to growth in soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In both vegetables, leaf explants did not respond well to growth regulators. BA alone or in combination with Indole Acetic Acid (IAA) or NAA is used for in vitro propagation and multiple shoot regeneration of other species (Avani et al, 2006;Sakpere et al, 2011;Sharma et al, 2009;Stojakowska and Malarz, 2004). This is the first report of vegetative propagation of C. volubile in which tip and softwood cuttings were found to be best for vegetative propagation.…”
Section: Discussionmentioning
confidence: 86%
“…In both vegetables, leaf explants did not respond well to growth regulators. BA alone or in combination with Indole Acetic Acid (IAA) or NAA is used for in vitro propagation and multiple shoot regeneration of other species (Avani et al, 2006;Sakpere et al, 2011;Sharma et al, 2009;Stojakowska and Malarz, 2004). This is the first report of vegetative propagation of C. volubile in which tip and softwood cuttings were found to be best for vegetative propagation.…”
Section: Discussionmentioning
confidence: 86%
“…Leaf explants that had generated roots on medium supplemented with 0.1 mg/l 2,4-D sub-cultured unto a medium supplemented with 0.1 mg/l 2,4-D and 1.0 mg/l Kinetin generated callus while leaf explants inoculated on medium supplemented with 0.5 mg/l Kinetin and 0.1 mg/l 2,4-D, generated compact, dark brown callus after which shoots emerged from the explant followed by more roots (Plate 1B). According to Stojakowska and Malarz (2004), the tendency to indirect organogenesis was diminished when Kinetin was used in cultures.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Media containing Benzyl adenine (BA) together with NAA have been reported to be preferably used for multiple shoot induction and maintenance in Asteraceae plants (Stojakowska and Malarz, 2004). According to Trejgell et This needs to be tested for Launea taraxacifolia since it is known that different species can respond differently to the same growth regulators.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Jabeen et al (2007) reported that the presence of auxin was necessary for roots induction on I. racemosa shoots and IBA was the most effective for this species. Stojakowska and Malarz (2004) used 0.02 mg l -1 IBA, which accelerated the rooting process, but had no effect on percentage of I. royleana rooted shoots. Moreover, the shoots of I. verbascifolia were rooted on MS medium supplied with 0.2 mg l -1 IBA (Thiem et al, 2003).…”
Section: Rooting and Acclimatizationmentioning
confidence: 99%
“…The species of Inula genus, I. viscose (Romano, 1997), I. royleana (Stojakowska and Malarz, 2004), I. verbascifolia transferred into plastic pots filled with a sterile mixture of vermiculite and sand (1:1). The plantlets from liquid medium were directly transferred to pots filled with the same substrate.…”
Section: Introductionmentioning
confidence: 99%